Case report: Nocardial brain abscess in a persistently SARS-CoV-2 PCR positive patient with systemic lupus erythematosus - Veličković, Jelena; Vukičević, Tatjana Adžić; Spurnić, Aleksandra Radovanović; Lazić, Igor; Popović, Bojana; Bogdanović, Ivan; Raičević, Savo; Marić, Dragana; Berisavac, Ivana (Frontiers in Medicine, 2022)
Coronavirus disease (COVID-19) in immunocompromised patients represents a major challenge for diagnostics, surveillance, and treatment. Some individuals remain SARS-CoV-2 PCR-positive for a prolonged period. The clinical and epidemiological significance of this phenomenon is not well understood. We report a case of a patient with a history of systemic lupus erythematosus (SLE) who has been persistently SARS-CoV-2 PCR positive for 9 months, with multiple thromboembolic complications, and development of nocardial brain abscess successfully treated with surgery and antibiotics.